2009
DOI: 10.1590/s0102-311x2009001100008
|View full text |Cite
|
Sign up to set email alerts
|

Saúde bucal de idosos residentes em instituições de longa permanência de Belo Horizonte, Minas Gerais, Brasil

Abstract: This study assessed the oral health of the institutionalized elderly in Belo Horizonte

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
(51 reference statements)
1
8
0
18
Order By: Relevance
“…Similar fact was observed by authors who explain that this may occur due to the presence of the ducts of salivary glands in this region, which provides a better irrigation, favoring the mechanical cleaning and the maintenance of the teeth in this sextant for a longer time (22,25) . It is important to focus on the fact that although a small sample represents a limitation for this study, it did not invalidate the findings that showed that PD is still severely present in elders despite the advances in Dentistry.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Similar fact was observed by authors who explain that this may occur due to the presence of the ducts of salivary glands in this region, which provides a better irrigation, favoring the mechanical cleaning and the maintenance of the teeth in this sextant for a longer time (22,25) . It is important to focus on the fact that although a small sample represents a limitation for this study, it did not invalidate the findings that showed that PD is still severely present in elders despite the advances in Dentistry.…”
supporting
confidence: 83%
“…Corroborating these findings, another research (25) has verified that the oral hygiene of dentulous elders was precarious. According to the authors, the idea that tooth loss is a natural consequence of ageing can lead the elderly to neglect oral hygiene measures.…”
Section: Discussionmentioning
confidence: 74%
“…When the adaptation is compromised, there may be: muscular and osseous instability; difficulties to speak, difficulties to chew and swallow, and decreased tasting sensation (14)(15)(16)(17) . In the present study, when the domains of the SWAL-QOL protocol were related to the adaptation of dentures (self-reported by the patient), it was possible to observe that there were differences in the domains "burden", "eating duration" and "frequency of symptoms".…”
Section: Discussionmentioning
confidence: 99%
“…The dental prosthetics emerged to solve this problem 16) , but the benefits depend directly on its adaptation (17) . The ill-adjusted denture, can create discomfort such as eating difficulty, alteration of speech intelligibility and esthetic dissatisfaction (17) . It is worth mentioning that there are variations within and between subjects, since aging and its change on quality of life do not elapse only from the biological process.…”
Section: Introductionmentioning
confidence: 99%
“…Há autores que afirmam que a doença periodontal, inclusive as bolsas periodontais, encontradas em grupos etários acima de 60 anos são, em sua maioria, mais severas VALSECKI JR, 2000;COSTA et al, 2010;FERREIRA et al, 2009 Frias et al (2011) realizaram um levantamento epidemiológico em uma população adulta na cidade de Guarulhos e concluíram que 9,1% da sua amostra apresentou sangramento gengival e em 53,6% foi observada a presença de cálculo.…”
Section: Iddunclassified